2016
DOI: 10.5005/ijifm-7-1-iv
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous 6 Months Oral Antioxidant Combination with Universally recommended Dosage in Idiopathic Male Infertility

Abstract: The aim of the present study was to observe the adverse effects of high level of reactive oxygen species (ROS) in idiopathic male infertility and the role of a combined antioxidant therapy for six months to overcome the detrimental effects of ROS. A prospective study including 185 infertile male was conducted at Institute of Reproductive Medicine (IRM) from January 2014 to April 2015. All the major sperm parameters as well as ROS, antioxidant level and the effect of high ROS level were evaluated before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…1 ) [ 12 13 14 15 ]. However, the outcomes of clinical trials included in the systematic reviews are not consistent, ranging from clear benefit to no clinical effect of the treatment, or even having significant detrimental effects [ 16 17 18 19 20 ]. The reasons for this inconsistency are multifactorial and include: small numbers of participants in the studies, variable treatment regimens, dosages, treatment duration, and the lack of placebo-controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [ 12 13 14 15 ]. However, the outcomes of clinical trials included in the systematic reviews are not consistent, ranging from clear benefit to no clinical effect of the treatment, or even having significant detrimental effects [ 16 17 18 19 20 ]. The reasons for this inconsistency are multifactorial and include: small numbers of participants in the studies, variable treatment regimens, dosages, treatment duration, and the lack of placebo-controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…These and numerous others are included in various registered AOX formulations [ 12 13 14 ] and food enriched with natural AOX [ 15 16 ]. Multiple studies have shown the benefit of AOX supplementation [ 17 18 19 ], and a recent Cochrane review found that oral AOX therapy may improve semen parameters and the likelihood of pregnancy [ 20 ]. However, the outcomes of clinical trials on the use of AOX in male infertility are not consistent, ranging from clear benefit [ 21 ] to no clinical effect [ 22 ], to even having significant detrimental effects [ 23 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Filipcikova et al in their study included 44 infertile men who were supplemented with lycopene for 3 months and found that seminal plasma's AA/DHA ratio improved in these cases [23]. Another study done by Chattopadhyay et al in 2016 showed an increase in motility and sperm count with a lowering of reactive oxygen species level, which gives a positive effect of Co Q10 on the participating patients [24]. Supplementation of omega-3 reduced DNA fragmentation, improved total antioxidant capacity (TAC) concentrations, and enhanced sperm motility as per studies done by Juan Carlos Martinex Soto et al and Gonzalez Ravina et al respectively [25,26].…”
Section: Discussionmentioning
confidence: 97%